4‐Heterosubstituted Cyclopentenone Antiviral Compounds: Synthesis, Mechanism, and Antiviral Evaluation. Issue 5 (15th January 2016) - Mantione, Daniele; Aizpuru, Olatz Olaizola; Memeo, Misal Giuseppe; Bovio, Bruna; Quadrelli, Paolo
Abstract: Racemic 4‐oxocyclopent‐2‐en‐1‐yl acetate was used in a short synthesis of nucleoside analogues with pyrimidine and purine heterobases. The protocol is based on a typical nucleophilic substitution process. Uracil, thymine, 6‐chloropurine, and some adenines gave the expected 4‐heterosubstituted products along with the isomeric 2‐heterosubstituted compounds as minor components. Samples of selected products were evaluated for their antiviral activity in a primary screening against a variety of viruses belonging to different classes. One of the compounds was found to be highly active against human papilloma virus (HPV). Abstract : Racemic 4‐oxocyclopent‐2‐en‐1‐yl acetate was used in a short synthesis of nucleoside analogues with pyrimidine and purine heterobases.